A separation logic for concurrent randomized programs - Tassarotti, Joseph; Harper, Robert (Proceedings of ACM on programming languages, 2019)
We present Polaris, a concurrent separation logic with support for probabilistic reasoning. As part of our logic, we extend the idea of coupling, which underlies recent work on probabilistic relational logics, to the setting of programs with both probabilistic and non-deterministic choice. To demonstrate Polaris, we verify a variant of a randomized concurrent counter algorithm and a two-level concurrent skip list. All of our results have been mechanized in Coq.